2021
DOI: 10.3389/fped.2021.642279
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telehealth on Clinical Education in Adolescent Medicine During the COVID-19 Pandemic: Positive Preliminary Findings

Abstract: Purpose: Following the start of the COVID-19 pandemic, much of clinical care rapidly transitioned to telehealth, shifting the clinical training milieu for most trainees. In the wake of this shift, educators have attempted to keep learners engaged in patient care and optimize medical education as much as possible. There is, however, limited understanding of the effect of telehealth on clinical education. The aim of our study was to better understand the educational experience of pediatric and Adolescent Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Our findings suggest that trainees in our Adolescent Medicine clinic have had positive learning experiences with telehealth and reported unique advantages that were often not afforded with in-person visits. Along with our recent work [ 17 ], this is the first study, to our knowledge, to evaluate the effects of telehealth in clinical education in Adolescent Medicine. Similar to prior studies, we found trainees had concerns about inability to observe pertinent physical exam skills during telehealth encounters, reported occasional discomfort holding difficult conversations virtually, and sometimes found it difficult to fit into the conversation [ 18 , 19 ••].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that trainees in our Adolescent Medicine clinic have had positive learning experiences with telehealth and reported unique advantages that were often not afforded with in-person visits. Along with our recent work [ 17 ], this is the first study, to our knowledge, to evaluate the effects of telehealth in clinical education in Adolescent Medicine. Similar to prior studies, we found trainees had concerns about inability to observe pertinent physical exam skills during telehealth encounters, reported occasional discomfort holding difficult conversations virtually, and sometimes found it difficult to fit into the conversation [ 18 , 19 ••].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, programs can consider creative ways of offering opportunities for remote, virtual USCE, considering subintern experiences, and inviting their matched IMG applicants for USCE prior to the internship start date. Psychiatry residency programs can also utilize telepsychiatry as a way of extending USCE to non-US IMGs [13].…”
Section: Challenge 3: Lack Of Opportunities For Clinical Experiencementioning
confidence: 99%
“…With recommendations regarding social distancing and judicious use of protective personal equipment, many residency programs have been embedding telepsychiatry in their training. Telepsychiatry has also emerged as a viable mode of providing care to patients, with both patients and mental health practitioners recording positive attitudes towards it [13,17]. Therefore, it is safe to assume that telepsychiatry will continue to exist as a mode of providing psychiatric care even when the pandemic recedes.…”
Section: Challenge 4: Unfamiliarity With Virtual Communication: Appli...mentioning
confidence: 99%
“…Berbagai penelitian dan survei yang dilakukan selama masa ini menemukan bahwa kepuasan yang tinggi terhadap telemedis yang diberikan [21]. Temuan pada penelitian ini konsisten dengan laporan ini [22], yang menunjukkan kepuasan tinggi dengan layanan telemedis.…”
Section: Analisis Hasil Akhirunclassified